Relationship between thick or greasy tongue-coating microbiota and tongue diagnosis in patients with primary liver cancer - Zhang, Yuren; Zhao, Hetong; Guo, Yuyu; Meng, Yongbin; Yu, Shasha; Pan, Bo; Zhai, Xiaofeng (Frontiers in Microbiology, 2022)
Tongue diagnosis is a unique aspect of traditional Chinese medicine for diagnosing diseases before determining proper means of treatments, but it also has the disadvantage of relying on the subjective experience of medical practitioners and lack of objective basis. The purpose of this paper is to elucidate tongue coating microbiota and metabolic differences in primary liver cancer (PLC) patients with thick or greasy tongue coatings. Tongue coating samples were collected from 60 PLC patients (30 PLC thick or greasy tongue coating patients and 30 PLC white tongue coating none thick nor greasy) and 25 healthy controls (HC). As compared to healthy individuals, tongue coatings of patients with PLC had elevated levels of Firmicutes and Actinobacteria. Abundance of Fusobacteria and SR1_Absconditabacteria_, Spirochaetae were higher in tongue coatings of healthy controls compared to samples in patients with PLC. In addition to site-specific differences, higher abundances of Fusobacteria and Actinobacteria were observed in thick or greasy tongue coating patients as compared to non-thick and greasy tongue coating patients. The inferred metagenomic pathways enriched in the PLC tongue coating patients were mainly those involved in replication, recombination and repair protein. We also identify a tongue coating microbiome signature to discriminate HC and PLC, including 15 variables on genus level. The prediction performance of the signature showed well in the training and validation cohorts. This research illustrates specific clinical features and bacterial structures in PLC patients with different tongue coatings, which facilitates understanding of the traditional tongue diagnosis.